Triggering fourth graders’ informal knowledge of isometric transformation geometry through the exploration of Malay cloth motif - Febrian, Febrian; Adi Perdana, Sukma (Journal of Educational Sciences, 2018)
Existing study revealed that the children have dynamics spatialsense on objects. One of important mathematics topics that can be related tothe sense-triggering process is the isometric transformation geometryincluding reflection, translation, and rotation. This topic is introduced to thefourth and the fifth graders of elementary school. However, learning processin school tends to lack concern on this students’ readily-triggered ability.There is also insufficient number of hands-on activities experienced by thestudents. It is poor since the hands-on activities can facilitate students’informal knowledge of isometric transformation geometry. Therefore, thistwo cycled design research aims to counter such situation. It was conductedat State Elementary School 001 of Toapaya, Kabupaten Bintan, KepulauanRiau by using RME approach. The subject of the study was the fourthgraders. Malay cloth motif was used as the context of the study through theexploration activities. The results indicated that the activities could triggerstudents’ informal knowledge of: reflection, translation, rotation, constantfactors, and transformation composition.